PENGELOLAAN BANTUAN SISWA MISKIN DI MTS NEGERI PADANG PANJANG - Emi Ratna Aprilana (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This research was aimed at describing the management of poor students’ subsidy (Bantuan Siswa Miskin/BSM) in MTs Negeri Padang Panjang related to (1) planning; (2) organizing on determination the receivers BSM; (3) briefing; (4) coordinating; and (5) supervising. This research was qualitative case study. The respondents of this research were the principal, committee, vice principal, administrator of BSM, and the receivers of BSM in 2015. Data reduction, data diplay and data conclusion were applied on analyzing data. The results obtained indicate that (1) the planning was appropriate with the technical instruction, it started from preparation meeting, quotas determination and collection; (2) the organizing was seen from the receivers’ mechanism based on the owner of KPS or SKTM, (3) the briefing was seen from the socializing BSM to the parents related to the benefit and usage of BSM; (4) the coordinating was done through distribution and usage mechanism should use Bank students’ account; and (5) the supervising was done by monitoring the usage should be appropriate with the program. The research concluded that the management of poor students’ subsidy in MTs Negeri Padang Panjang was run well but it needs more socialization and consider the transparancy, effectivity and effiency.Keywords: Management, Poor Students’ Subsidy (BSM), MTs Negeri, Padang Panjang